In My Element: Manganese. Issue 25 (8th April 2019) - Pumera, Martin
Abstract : The In My Element series celebrates the personal accounts from Chemistry – A European Journal Editorial Board members for the 2019 International Year of the Periodic Table. In this contribution, Martin Pumera gives his story on manganese.